Imagining viral hepatitis in Burkina Faso - (:unkn) unknown (My University, 2020)
This article explores ‘imaginings’ around hepatitis B in Burkina Faso and their historical genealogies. Hepatitis B is a viral infection afflicting the liver, but asymptomatic carriers may fall ill decades after exposure to the virus. Drawing from ethnographic interviews, we analyse how people living with hepatitis B in Burkina Faso grapple with incertitude about the course of their infections, the possibilities for healing and their illness’s influence on social relations by ‘imagining’: that is, diverging momentarily from narratives about their diagnostic and therapeutic pathways to imagine alternative pasts and future consequences of this illness. We investigate how those living with hepatitis B use these imaginings to grapple with absences – of a certain future, of knowledge and of care – the historical genealogies that give rise to these absences, and their longer-term consequences. These ephemeral imaginings emerge from an ‘entanglement’ of the virus, epidemiological incertitude about its course and absences within Burkina Faso’s health system and global health policies, which are themselves the consequence of specific historical processes.
Keywords: African Research